2018
DOI: 10.1051/mbcb/2017027
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary ameloblastoma: results of the treatment in 11 patients

Abstract: Introduction: Surgery of maxilla ameloblastoma is mutilating and the tumor propensity for recurrence high. Patients and Methods: The oral and visual functions, facial morphology and tumor recurrence in 11 patients after maxillary ameloblastoma surgery are retrospectively reviewed. Results: Facial morphology was satisfactory in 7 patients who had all tumor removal by a type 1 or 2A maxillectomy and surgical wound closure. Out of these patients, 4 who had dental rehabilitation by conventional prosthesis presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
0
1
Order By: Relevance
“…When comparing ameloblastoma in the maxilla to those in the mandible, numerous authors reported that maxillary lesions tend to occur more frequently in males with an average age of 54.9 years [3,15]. This is in contrast to mandibular lesions in this study which occurred nearly equally in males and females with a lower mean age of 32.99 years.…”
Section: Discussioncontrasting
confidence: 70%
“…When comparing ameloblastoma in the maxilla to those in the mandible, numerous authors reported that maxillary lesions tend to occur more frequently in males with an average age of 54.9 years [3,15]. This is in contrast to mandibular lesions in this study which occurred nearly equally in males and females with a lower mean age of 32.99 years.…”
Section: Discussioncontrasting
confidence: 70%